Black carbon aerosols in urban central China. (January 2015) - Zhang, Xiaolin; Rao, Ruizhong; Huang, Yinbo; Mao, Mao; Berg, Matthew J.; Sun, Wenbo
Abstract: The first ever (to our knowledge), year-round measurements of Black Carbon (BC) aerosols in Hefei, an urban site of central China, from June 2012 to May 2013 are performed. The aim of this paper is to evaluate the black carbon in Hefei in terms of seasonal, monthly and diurnal variations, including their source identification. The annual mean BC mass concentration M BC is found to be 3.5±2.5 μg m −3 in Hefei, while the aerosol optical depth shows a yearly average value of ~0.6. The seasonality of M BC depicts minimum values in the summer, moderate levels in the spring and fall, and maximum in the winter. The monthly average values of M BC vary threefold, ranging from the lowest average value of 2.0±1.0 μg m −3 in July to the highest 6.0±2.6 μg m −3 during January. Diurnal variations exhibit two BC peaks, corresponding to the morning and evening rush hours. Higher median BC concentrations are observed during haze episodes compared with non-haze periods, although low M BC is sometimes observed for high visibility, which is probably indicative of the aerosol scattering dominating diminished visibility. Based on trajectory analyses, the haze BC pollutions are mostly classified into three types from local areas, long-range transport from the Yangtze Delta, and transport from the North China Plain. The median M BC values for haze groups attributed to biomass burning from MODIS wildfire maps are higher than related groups that are not, which is indicative of the significant enhancement of BC aerosols due to agricultural biomass burning. The study suggests that aerosol absorption contributes more to the observed haze episodes in fall compared to other seasons. Highlights: Year-round measurements of black carbon aerosols in Hefei were presented. Black carbon mass concentrations during haze episodes were evaluated. Source identification of black carbon over Hefei was estimated. Aerosol absorption contributes more to the observed haze episodes in fall.